‘A Right to Water’ in International Human Rights Law: Flow from Implicit to Explicit Right - Sangroula, Swechhya (Kathmandu School of Law Review, 2017)
The paper relies on doctrinal method of study in determining whether a right to water exists under international human rights law. As primary source, the paper relies on the International Covenant on Economic, Social and Cultural Rights and the products of the ICESCR’s monitoring system: Economic and Social Council (ECOSOC) and particularly the work of the CESCR, which is the subsidiary body of the ECOSOC, tasked with monitoring functions, since 1985. The paper relies on the international interpretation of relevant ICESCRprovisions made by the CESCR as ‘evidence of the meaning and application of the Covenant’.1 The paper also relies on the study of relevant Concluding Observations issued by the CESCR during the course of its monitoring of states’ periodic reports. The primary reason, being, that unlike ICCPR’s Human Rights Committee jurisprudence, the ICESCR has not developed a body of jurisprudence from its treaty body. As secondary sources, scholarly writings and published academic debates have been referred to gauge the contents of the academic debate surrounding the issue.